THE ROLE OF QUALITY PRODUCTION IN ENTERPRISES - Badalov Nomoz Juraboyevich; Badalov O’tkirbek Nomoz Son (Galaxy International Interdisciplinary Research Journal, 2021)
In the production of quality products it is necessary to provide information on international, interstate, regional standards, state standards of the Republic of Uzbekistan, national standards of foreign countries, rules, norms and recommendations of standardization. A product is a materialized result of the process of labor activity, which has useful properties, is obtained in specific production processes and is designed to meet the needs of a particular community and individual.